Fish Abundance In South Poigar Rivermouth South Minahasa - Nuske Kamurahan; Nego E. Bataragoa; Anneke V. Lohoo (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2022)
The objective of the study is to know the fish individual abundance and biomass in the mouth of Poigar River. The study employed swept area method, sampling was done at high tide and low tide of a new moon and full moon phase using a beach seine. The seine covered 2700 m2 at low tide and 900 m2 at high tide. The fish catches in both moon phases and tidal conditions consisted of 40 species of 25 families and 481 individuals. Total fish weight was 3,804 g. The individual abundance in the new moon was 0.0004/m2 – 0.1200/m2, and the biomass in the new moon was 0.0002 g/m2 – 0.5044 g/m2. The individual abundance in full moon was 0.0004/m2 – 0.0622/m2, and the biomass in full moon was 0.0002 g/m2-0.4017 g/m2. As a whole, both individual abundance and biomass in new moon and full moon at were 0.3922g/m2  and 2.7778 g/m2, respectively.Keywords: abundance, biomass, river poigar.AbstrakTujuan penelitian yaitu untuk mengetahui kelimpahan individu dan biomassa penelitian ini menggunakan metode (swept area), pengambilan sampel dilakukan saat air surut dan air pasang pada fase bulan baru dan bulan purnama dengan menggunakan pukat pantai. Luas daerah sapuan pukat pada periode surut 2700 m2 dan periode pasang 900 m2. Hasil tangkapan selama dua periode bulan saat air pasang maupun air surut sebanyak 40 spesies ikan dari 25 famili, 481 individu dan berat 3804. Ki bulan baru 0,0004/m2-0,1200/m2, Kb bulan baru 0,0002g/m2-0,5044g/m2. Ki bulan purnama 0,0004/m2-0,0622/m2, Kb bulan purnama 0,0002g/m2-0,4017. Secara keseluruhan kelimpahan individu dan biomassa pada fase bulan baru dan bulan purnama saat air surut dan pasang adalah Ki sebesar 0,3922/m2 sedangkan Kb sebesar 2,7778 g/m2.kata kunci: Kelimpahan, biomassa, sungai poigar